Complication Rates and Maintenance of Correction After 3-Column Osteotomy in the Elderly: Report of 55 Patients With 2-Year Follow-up. Issue 5 (21st December 2017) - Challier, Vincent; Henry, Jensen K; Liu, Shian; Ames, Christopher; Kebaish, Khaled; Obeid, Ibrahim; Hostin, Richard; Gupta, Munish; Boachie-Adjei, Oheneba; Smith, Justin S; Mundis, Gregory; Bess, Shay; et al.
Abstract: BACKGROUND: Three-column osteotomies (3CO) provide substantial correction for adult spinal deformity (ASD), but carry risks of complications and revisions. The risk-benefit balance of 3CO in the elderly remains unclear. OBJECTIVE: To evaluate sagittal alignment and complications after 3CO in a population over 70-yr old. METHODS: Radiographic retrospective review of consecutive patients over 70 yr ("Elderly") undergoing 3CO for ASD. Demographic, operative, and outcomes data were collected. Full-spine radiographs were analyzed at baseline and 2-yr postoperatively. Results were compared to a group of young controls ("Young") matched by global sagittal alignment. RESULTS: Elderly (n = 55) and Young (n = 52) were similar in operating room time, blood loss, levels fused, and revision surgeries. Elderly and Young groups had similar baseline radiographic malalignment for pelvic tilt, pelvic incidence−lumbar lordosis (PI-LL), and sagittal vertical axis ( P > .5 for all). At 2-yr postoperatively, both groups underwent significant improvement in the setting of sagittal alignment parameters (Elderly: sagittal vertical axis 150 mm to 59 mm, P < .001; pelvic tilt 33° to 25°, P < .001; PI-LL 35° to PI-LL 6°, P < .001). However, the Elderly group underwent significantly greater correction in PI-LL than the Young group (−29° vs −20°, P = .024). There were no differences in total, intraoperative or postoperative complications or revisions between groups, though the Elderly group had more intraoperative complications when major blood loss was included. The Elderly group had more severe proximal junctional kyphosis (22.1° vs 9.6° in Young; P < .001). CONCLUSION: Compared to young patients, elderly patients may achieve the same, or even better, correction in radiographic spinopelvic parameters. In addition, not only the total intraoperative and postoperative complication rates but also revision rates were comparable between both groups.